VOLUME DAN KLASIFIKASI LIMBAH EKSPLOITASI HUTAN - Sampe Radja Simarmata; Haryono Haryono (Jurnal Penelitian Hasil Hutan, 1986)
The aim of the study is to estimate the volume of waste producted by forest  exploitation in the cutting area and toclassific of logging waste based on their source. The kind of logging waste based on their sources consist of : Waste come from there which to be cut and divided of bole (tunggak) remained stem (batang) becouse of bucking and stem up to the first branchDamage trees have been coused by influence of both cutting and yardingThe meaning of waste in the study in stem and branches with diameter up 10 cm and lenght up 1 m and length of bole do not depend on the size.  ·  Data analyisis used statistical method. The methode was analyisis of variance based on Bartlett test.Average of waste volume per ha is 18.935 m3ha consist of source of cutting trees  57.12 % effecting of cutting.38.13 % and effecting of yarding 4.16 %.In order to decrease waste and enhance resource efficiency, quickly make methode to solve problem with integratedsurvey between departments which connect with their problem forest companies and population sourounded area.